Pelestarian Dan Pengembangan Makanan Khas Kampung Ciharahas Mulyaharja Sebagai Destinasi Wisata Kota Bogor - Asep Parantika; Gaby Jenica (STIE Pariwisata API Yogyakarta, 2022)
Indonesia also has a variety of traditional culinary. The city is one of the cities that has a unique gastronomic tourism with a variety of special foods. Mulyaharja Village, which is the main tourist attraction of Bogor, also offers a variety of special foods found in Sundanese specialties. However, there are still many people who do not know the typical food of Mulyaharja Village. This study aims to explain what factors make Mulyaharja village a tourist destination in the city of Bogor and to find out the typical food of Mulyaharja Village which has the potential to become a source of income for residents. The data for this study were collected through observation and interviews with several sources. The data analysis tool used is the SWOT matrix to identify internal and external factors. The results of the study show that, first, Mulyaharja Village already has the factors that make it a tourist destination. However, there are still some limitations that need to be developed. Second, Mulyaharja Village has unique traditional food, namely Nasi Liwet, Nasi Tutung Oncom, Stir-fried Banana Heart, Jengkol Balado and Cucumber Shaved Ice. Third, the typical cuisine of Mulyaharja village can be a source of community income, namely by increasing promotion facilities and maintaining and improving the quality of Mulyaharja's culinary specialties. That way, Mulyaharja Village can become one of the culinary tourism spots in the city of Bogor.